INTERPROFESSIONAL COLLABORATION AND HEALTHCARE ORGANIZATION: an exploratory investigation into the challenges and opportunities for rehabilitation professionals. - Simone Sottana; Andrea Vianello; Matteo Tognin; Deborah Mazzarotto; Marco Ceccato; Daria Visintin; Riccardo Martignon; Francesca Magaton Rizzi; Noemi Pasquon; Lucia Savietto (Journal of Biomedical Practitioners)
Introduction: In the past five years, interprofessional collaboration within the rehabilitation sector has gained significant prominence in the Italian context, emphasizing the efficacy of collaborative methodologies in the treatment of patients with complex disabilities. The recognition of eight rehabilitation professions classified under the first cycle degree class L/SNT2 (Health Professions) has established a foundation for a patient-centered and multiprofessional model of care. However, comprehensive studies regarding the perceptions and implementations of interprofessional collaboration in Italy are notably absent, creating a substantial gap in academic literature and presenting numerous avenues for future inquiry.